Hubungan Nilai Hematokrit dengan Jumlah Eritrosit pada Pasien Demam Dengue di Rumah Sakit Bhayangkara Kota Kediri - Nita Ermawati; Erawati Erawati; Yuliya Tyas Ismawanti (Jurnal Anestesi, 2025)
Dengue fever (DF) and dengue haemorrhagic fever (DHF) are infectious diseases caused by the dengue virus through the bite of aedes aegypti mosquitoes with clinical manifestations of fever, muscle or joint pain accompanied by leukopenia, rash, lymphadenopathy, thrombocytopeniaan dhemorrhagic dermatitis. Based on data from the Ministry of Health in 2020 in Indonesia until July, there were 71,700 cases. In addition, the number of deaths throughout Indonesia reached 459. However, the number of cases and deaths this year is still low comparedto 2019.This study aims to determine the relationship between hematocrit value and erythrocyte value in dengue fever patients at Bhayangkara Hospital, Kediri City. The sampling technique used was total sampling with a sample of 20 samples. Based on the results of the examination of hematocrit values with erythrocyte values in dengue fever patients at Bhayangkara Hospital, Kediri City in 25 June - 10 July 2024 from 20 samples obtained the results of low hematocrit 10 (50%) normal hematocrit 8 (40%) high hematocrit 2 (10%) and lowery throcytes 8 (40%) normalery throcytes 8 (40%) highery throcytes 4 (20%).